Tics, ADHD and Psychiatric Comorbidity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The prevalence of teacher-rated tic behaviors in 3006 school children, from preschool to adolescence, was determined in a study of comorbid psychiatric symptoms at State University of New York, Stony Brook, NY.